(untitled) (Revista NUPEART, 2021)
This article reports the creative processes in theater that were carried out with two 9th grade classes, in Curitiba, Paraná. Such processes were developed connecting the themes related to diversity, prejudice, genderrelated questions and especially the questions related to women, drawing on the aesthetics of the Theatre of the Oppressed of Augusto Boal, specifically the Image Theater and the Newspaper Theater. The process was divided in two steps, with the total of twenty meetings, accomplished between February and December, 2017 ive thinking that reached three creative processes in theater. The literature review presented concerns the theories related to gender studies, theater teaching in primary and secondary school and the Theatre of the Oppressed. For that, it was used as a main literature contribution the authors Augusto Boal, Judith Butler and Guacira Lopes Louro.